2014
DOI: 10.1016/j.schres.2014.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of antipsychotic medication in pregnancy: A cohort study

Abstract: Pregnancy was a major determinant of cessation of antipsychotics. Only 38% of women on atypical and 19% on typical antipsychotics were still prescribed the drug in the third trimester. Duration of prior treatment, maternal age as well as dose was significantly associated with continued treatment of antipsychotics in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 18 publications
3
35
2
Order By: Relevance
“…The discontinuation patterns observed in this study were similar to the results from previous studies in the UK in which close to 50% of women had discontinued atypical antipsychotics by six weeks of pregnancy and 62% to 72.3% by the third trimester (19, 22). Interestingly, a greater number of women filled a prescription for a typical antipsychotic after LMP compared to the baseline period; a similar trend was not seen for atypical antipsychotics.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The discontinuation patterns observed in this study were similar to the results from previous studies in the UK in which close to 50% of women had discontinued atypical antipsychotics by six weeks of pregnancy and 62% to 72.3% by the third trimester (19, 22). Interestingly, a greater number of women filled a prescription for a typical antipsychotic after LMP compared to the baseline period; a similar trend was not seen for atypical antipsychotics.…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of women on antipsychotic treatment during pregnancy in our study is higher than that found in European cohorts (range .1% to .3%) or privately insured women in the US (.7% for atypical antipsychotics) during partly overlapping periods (1822). This is not surprising, because the prevalence of mental illness is known to be higher for the Medicaid insured population, due partly to the lower socioeconomic status and higher proportion of minority groups (23).…”
Section: Discussioncontrasting
confidence: 79%
“…Parts of this work have been published elsewhere. 46,47 Prevalence of psychotropic treatment before, during and after delivery…”
Section: Resultsmentioning
confidence: 99%
“…12,18,20 In this project we demonstrated that the majority of these women discontinue psychotropic medication either before or in early pregnancy. 46,47 For each individual woman this is likely to result from an informal 'risk-benefit' evaluation, which may include a range of factors such as previous medical history, current state of illness, likelihood of relapse in pregnancy and postpartum, family circumstances, known teratogenic risks and fear of doing harm to the unborn child. 4,14,20 For some women the answer to this evaluation is 'clear-cut' with the benefits of continuing treatment in pregnancy noticeably outweighing the potential risks.…”
Section: Risks and Benefits Of Psychotropic Medication In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation